Soil susceptibility to accelerated hydric erosion: geotechnical evaluation of cut slopes in residual soil profiles (Acta Scientiarum. Technology, 2015)
The experimental research program was developed in the Alto Paraopeba region, state of Minas Gerais, Southeastern Brazil. The main objective was to promote the geotechnical evaluation of soil samples from four cut slopes in residual soil profiles of highways and local secondary roads in order to assess the potential of the anthropic impact on the soil susceptibility to accelerated erosion processes. Soil samples were named: red residual soil (RRS); pink residual soil (PRS); yellow residual soil (YRS); and white residual soil (WRS). The methodology used consisted of geotechnical characterization tests, infiltration rate and modified mass loss by immersion tests performed on soil samples from these profiles, using the physical parameters and indirect assessment of erodibility proposed in 2000 by Bastos et al. The results of indirect assessment of erodibility, which were derived from tests based on the MCT methodology, highlighted the different susceptibility of the investigated soils to hydric erosion. The parameters proposed by the referred authors were complementary to conventional criteria for an adequate classification of tropical soils into their respective classes of erodibility. Among the tested soil samples, the highest erodibility was associated with the YRS and PRS, respectively, in the natural and pre-moistened conditions, as well as it was not detected erodibility in the RRS and WRS.Â